Disease and demographic development: the legacy of the plague - Fabian Siuda; Uwe Sunde (Journal of Economic Growth, 2021)
This paper provides an empirical investigation of the hypothesis that population shocks such as the repeated outbreaks of the plague affected the timing of the demographic transition. The empirical analysis uses disaggregate data from Germany and exploits geographic variation in the exposure to medieval plague shocks. The findings document that areas with greater exposure to plague outbreaks exhibited an earlier onset of the demographic transition. The results are consistent with the predictions of the unified growth literature and provide novel insights into the largely unexplored empirical determinants of the timing of the transition from stagnation to growth.
Keywords: O10; J10; 330; Plague; Demographic transition; Fertility; Outbreak; Epidemics